2004
DOI: 10.1128/jb.186.9.2612-2618.2004
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Linear-Plasmid-Encoded Factor H-Binding Protein (FhbA) of the Relapsing Fever Spirochete Borrelia hermsii

Abstract: In North America, tick-borne relapsing fever (TBRF) is caused by the spirochete species Borrelia hermsii, Borrelia parkeri, and Borrelia turicatae. We previously demonstrated that some isolates of B. hermsii and B. parkeri are capable of binding factor H and that cell-bound factor H can participate in the factor I-mediated cleavage of C3b. Isolates that bound factor H expressed a factor H-binding protein (FHBP) that we estimated to be approximately 19 to 20 kDa in size and thus, pending further characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
116
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(119 citation statements)
references
References 29 publications
2
116
1
Order By: Relevance
“…The previous findings that the relapsing fever spirochete B. hermsii expresses a receptor for FH, FhbA, and that surface-bound FH facilitates factor I-mediated cleavage of C3b suggest a suitable strategy of the pathogen to evade the first-line host defense via the complement system (18). FH binding has been reported for a number of bacterial species such as S. pyogenes (group A streptococcus) (50), Neisseria gonorrhoeae (10, 51), S. pneumoniae (11,13,52), B. burgdorferi (24), Borrelia afzelii (25), Borrelia recurrentis (53), Borrelia duttonii (53), Borrelia parkeri (17), and B. hermsii (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous findings that the relapsing fever spirochete B. hermsii expresses a receptor for FH, FhbA, and that surface-bound FH facilitates factor I-mediated cleavage of C3b suggest a suitable strategy of the pathogen to evade the first-line host defense via the complement system (18). FH binding has been reported for a number of bacterial species such as S. pyogenes (group A streptococcus) (50), Neisseria gonorrhoeae (10, 51), S. pneumoniae (11,13,52), B. burgdorferi (24), Borrelia afzelii (25), Borrelia recurrentis (53), Borrelia duttonii (53), Borrelia parkeri (17), and B. hermsii (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…FH binding has been reported for a number of bacterial species such as S. pyogenes (group A streptococcus) (50), Neisseria gonorrhoeae (10, 51), S. pneumoniae (11,13,52), B. burgdorferi (24), Borrelia afzelii (25), Borrelia recurrentis (53), Borrelia duttonii (53), Borrelia parkeri (17), and B. hermsii (18,19). Moreover, for B. hermsii YOR it was found that it specifically binds both FH and FHL-1 via FhbA and that FH and FHL-1 interact with FhbA through the SCR domains 1-7 and SCR16 -20 (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR and ligation-independent cloning of FhbA were performed as described by Marconi and colleagues (6). Plasmids were transformed into Escherichia coli NovaBlue cells (Novagen), and sequence analysis of the inserts was performed by Thomas Jefferson University's Nucleic Acid Core Facility.…”
Section: Recombinant Expression Of Fhba1 or Fhba2 Of B Hermsiimentioning
confidence: 99%
“…The random expression of different Vmps during infection results in the outgrowth of new serotypes and allows evasion of the adaptive immune response. Recently, a strategy by which B. hermsii also evades the innate immune system has been proposed (6). This is based on the ability of B. hermsii to bind factor H, a serum complement regulatory protein.…”
mentioning
confidence: 99%